Meltdown London debut of the Moscow Stanislavsky Ballet - Bissell, Bill (Dance Books Ltd., Alton,Hampshire (UK), 2002)
London debut of the Moscow Stanislavsky Ballet. PALABRAS CLAVE: Moscow Stanislavsky Ballet, Russian company, The Snow Maiden, Vladimir Bourmeister, Swan Lake.